2022
DOI: 10.1089/omi.2022.0108
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Explaining Outcomes in Africa: Could Genomic Variation Add to the Debate?

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent of COVID-19, emanated from the Wuhan Province in China and rapidly spread across the globe causing extensive morbidity and mortality rate, and affecting the global economy and livelihoods. Contrary to early predictions of “body bags” across Africa, the African COVID-19 pandemic was marked by apparent low case numbers and an overall mortality rate when compared with the other geographical regions. Factors used to describe this u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…We observed that countries in Africa have great variation in socioeconomic and COVID-19 health vulnerabilities. These results are likely related to a difference in the ability of countries to detect and test patients, limited PPE availability, the high prevalence of younger population, a lack of rapid and more effective national health policies, and the possibility of under reporting of cases and deaths (48). This finding was also reported in similar related studies (49,50,51).…”
Section: Discussionsupporting
confidence: 53%
“…We observed that countries in Africa have great variation in socioeconomic and COVID-19 health vulnerabilities. These results are likely related to a difference in the ability of countries to detect and test patients, limited PPE availability, the high prevalence of younger population, a lack of rapid and more effective national health policies, and the possibility of under reporting of cases and deaths (48). This finding was also reported in similar related studies (49,50,51).…”
Section: Discussionsupporting
confidence: 53%
“…Concurrently, factors intrinsic to the African population are being discussed to be causative for a lower morbidity and mortality on the continent, such as the general younger demographic of the population, lack of diagnosis in cases of deaths, genetic factors [108], the increased circulation of other coronaviruses having a protective effect against critical COVID-19 [108,109], or the higher burden of other infectious diseases such as malaria leading to an increased alertness of the innate immune system and consequently a lower morbidity and mortality [110].…”
Section: Sars-cov-2 Infection Detection Rate In the African Populatio...mentioning
confidence: 99%
“…The factors contributing to these low death rates in Africa, despite a weak healthcare infrastructure, have drawn fierce debate and raised big questions among scholars and civic leaders [2][3][4][5][6]. Several hypotheses have been provided to support the low reported death rates and case fatality rates, such as low vaccine coverage and/or underreporting [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%